Formative research on a teacher accompaniment model to promote youth mental health in Haiti: Relevance to mental health task-sharing in low-resource school settings. (June 2017) - Eustache, Eddy; Gerbasi, Margaret E; Severe, Jennifer; Fils-Aimé, J Reginald; Smith Fawzi, Mary C; Raviola, Giuseppe J; Darghouth, Sarah; Boyd, Kate; Thérosmé, Tatiana; Legha, Rupinder; Pierre, Ermaze L; Affricot, Emmeline; et al.
Background: Task-sharing with teachers to promote youth mental health is a promising but underdeveloped strategy in improving care access in low-income countries. Aims: To assess feasibility, acceptability and utility of the teacher accompaniment phase of a school-based Teacher- Accompagnateur Pilot Study (TAPS) in Haiti. Methods: We assigned student participants, aged 18–22 years ( n  = 120), to teacher participants ( n  = 22) within four Haitian schools; we instructed participants to arrange meetings with their assigned counterparts to discuss mental health treatment, academic skills, and/or well-being. We measured student and teacher perceived feasibility, acceptability and utility of meetings with self-report Likert-style questions. We examined overall program feasibility by the percentage of students with a documented meeting, acceptability by a composite measure of student satisfaction and utility by the percentage with identified mental health need who discussed treatment with a teacher. Results: Favorable ratings support feasibility, acceptability and utility of teacher- accompagnateur meetings with students. The majority of students (54%) met with a teacher. Among students with an identified mental disorder, 43.2% discussed treatment during a meeting. Conclusion: This accompaniment approach to mental health task-sharing with teachers provided a school-based opportunity for students with mental health need to discuss treatment and has potential relevance to other low-income settings.